Penicillin Use in Meningococcal Disease Management: Active Bacterial Core Surveillance Sites, 2009. (13th July 2016) - Blain, Amy E.; Mandal, Sema; Wu, Henry; MacNeil, Jessica R.; Harrison, Lee H.; Farley, Monica M.; Lynfield, Ruth; Miller, Lisa; Nichols, Megin; Petit, Sue; Reingold, Arthur; Schaffner, William; et al.
Abstract: In 2009, in the Active Bacterial Core surveillance sites, penicillin was not commonly used to treat meningococcal disease. This is likely because of inconsistent availability of antimicrobial susceptibility testing and ease of use of third-generation cephalosporins. Consideration of current practices may inform future meningococcal disease management guidelines.